Does legitimacy matter in whistleblowing intentions? - Mbago, Musa; Ntayi, Joseph; Mutebi, Henry (International Journal of Law and Management, 2018)
Despite the introduction of Whistleblowers Act in 2010 to create an enabling environment for Ugandan citizens to freely disclose information on unethical practices or improper conduct in the public and private sectors, the percentage of people reporting unethical practices continue to be small. The Afro Barometer survey of 2015 reveals that out of the 2400 respondents surveyed in the public sector, only 6% reported unethical incidents in the public sector to government officials or people in authority while the remaining 94% remained morally mute. This is consistent with the results of the Economic Policy Research Center (2009) which rated Uganda low on the reporting of unethical practices. This finding is corroborated by the Inspectorate of Government which reports having received only 1,000 complaints from the public in 2014 (The Observer, 2014). These revelations could be attributed to legitimacy challenges which often result in retaliatory actions such as firing, blacklisting, threats, harassment, physical violence and verbal abuse, transfer, dismissal and humiliation of whistleblowers. There are a number of reports which support retaliatory practices in public procurement. According to “The 3rd Public Procurement Integrity Survey Report of (2016), 9.9% of the respondents indicated that they chose to keep quiet about the misdeeds of the public officials because of fear of victimization as the wrongdoers command high social status in the public sector. Cases supporting this conduct include; a whistleblower who lost his job in the Office of the Prime Minister (OPM) after reporting a procurement related scam. The identity of the whistleblower was revealed resulting in malice and personal vendetta.
Keywords: Legitimacy matter; Whistleblowing intentions